Issue-Choice, Messaging, and Organizing: A Sociological Approach to Three Ballot Measures in Colorado in 2006 - Guillaume Marche (Transatlantica)
This article examines the coincidence of apparently contradictory ballot measure results in Colorado in 2006 as a case study of the significance of this form of direct democracy for progressive social movements: are ballot measures an opportunity or a hindrance for progressive organizing? Based on qualitative fieldwork in Denver in March and April 2008, we use framing theory to argue that whether ballot measure campaigns divert the action of social-movement organizations from their long-term goals, or allow them to pursue them by empowering voters is more dependent on the forms of organizing, than on issue-choice or messaging.